Sensitivity testing study proposed by method and apparatus for determining muscle imbalances at the trunk level - Zenovia, S.; Batiurega, E.; Rizescu, C. (Science, Movement & Health, 2015)
The purpose of this study is to determine whether the measurements made with the device for determining muscle imbalances present in the trunk are significantly delimited by age, in order to demonstrate the sensitivity of the proposed tests. Methods. The study was conducted on 120 subjects aged from 6 to 18 years. The total sample is divided into six groups, with age as the independent variable, as follows: 6, 7, 12, 14, 16 and 18 years old. 9 tests were applied to measure muscle strength in the trunk as follows: testing of the flexion muscle strength from sitting; testing of the flexion muscle strength on the left side slope from sitting; testing of the extension muscle strength from sitting; muscle strength testing on the right side slope, from sitting; flexion muscle strength testing of standing; muscle strength testing on left lateral tilt of standing; muscle strength testing the extension from standing; muscle strength testing on the right side slope of standing; lumbar muscle strength testing (classic test). Unifactorial dispersion analysis is used (One Way ANOVA); the method by which the multiple comparisons are done by repeated measurements. Result. Mauchly's test results Test of sphericity is not statistically significant (p>0.05) and therefore the spherical condition is met. All values of F are greater than 0.05 then the null hypothesis is rejected. Conclusions. All tests have a significant sensitivity taking into account differences between subjects; in this case the independent variable is age. It highlights the differences between groups and differences between subjects in each group. Null hypothesis is rejected and the alternative hypothesis is accepted that media groups are significantly different from each other and not due to chance alone.